2013
DOI: 10.1039/c3ob27204d
|View full text |Cite
|
Sign up to set email alerts
|

From G-quartets to G-ribbon gel by concentration and sonication control

Abstract: Two guanosine analogues have been designed and synthesized by connecting one (1) or three adamantane branches (2). The compound containing a single adamantane branch formed G-quartets in acetonitrile solution, and was then transformed into a G-ribbon gel at concentrations higher than the critical gelation concentration. In contrast, the compound with three adamantane branches precipitated after a heating-cooling process. By means of circular dichroism and UV/visible spectra, NMR, SEM, and structural studies, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Recently, Yi et al. showed that the conversion between G 4 and G‐ribbon structures could be controlled reversibly by varying the concentration of G in solution and that gels were formed with ribbon structures at higher concentration . Similar experimental findings of ring and ribbon structures were obtained for X derivatives in solution, as well as self‐assembled nanostructures on gold surfaces …”
Section: Introductionmentioning
confidence: 62%
“…Recently, Yi et al. showed that the conversion between G 4 and G‐ribbon structures could be controlled reversibly by varying the concentration of G in solution and that gels were formed with ribbon structures at higher concentration . Similar experimental findings of ring and ribbon structures were obtained for X derivatives in solution, as well as self‐assembled nanostructures on gold surfaces …”
Section: Introductionmentioning
confidence: 62%
“…a | Amphiphilic guanosine (G; 2) that self-assembles into a lyotropic liquid crystal triggered by a K + -promoted synthetic G-quartets (SQ) formation 96 . b | Cation-free SQ formed by adamantyl-conjugated guanines (13) 99 , whose SQ/ribbon topological transition is controlled by the concentration.…”
Section: G-quartet-based Soft Mattermentioning
confidence: 99%
“…8b). Gelation occurred when ribbons selfassembled into micrometrewidth hexa gonal columnar structures; a morphological change can be triggered by ultrasonication, which favours twistedflowerlike structures 99 . Liu and colleagues observed a similar behaviour with a guanine function alized with a 3,4,5tris(ndodecan1yloxy)benzohy drazide (14): the quartettoribbon structural transition was solventdependent, occurring above 17% w/w in toluene and above 29% w/w in chloroform.…”
Section: Wwwnaturecom/natrevchemmentioning
confidence: 99%
“…Dyes were added to visualize the gels. 11 BNMR of c) ChCl/MPG and d) ChCl/GL eutectogel, suggesting only guanosine/boric acid (GB) diester signals were observed in ChCl/MPG eutectogel, whereas both GB monoestera nd GB diester signals were observed in ChCl/GL eutectogel.…”
Section: Resultsmentioning
confidence: 99%
“…To further reveal the formation mechanism of the eutectogels,variable-concentration and variable-temperature 11 BNMR experiments were performed. Ther atio of GB monoester and GB diester in ChCl/GL eutectogel has been qualitative determined by the ratio of their relative integral area.…”
Section: Methodsmentioning
confidence: 99%